Significance of Sriwijaya Kingdom to Negeri Sembilan traditional architecture / Mawar Masri and Shamsidar Ahmad - Masri, Mawar; Ahmad, Shamsidar (2012)
This paper seeks to present the findings of a comprehensive literature review of the historical studies of Negeri Sembilan, Malaysia. The study identifies the derived values from Sriwijaya Kingdom maritime culture hence their significance to the traditional architecture of Negeri Sembilan, hence further refines the methodology framework towards determining the authenticity. The research which this paper is based on aimed at analyzing the traditional architecture of Rembau, Negeri Sembilan. The methodology is qualitative. The literatures revealed that the Malays, known as the creators of ships, magnificent skills in sailing and navigational field proudly manifested this identity into their architecture.